Prediction of overbite improvement in deep bite correction using clear aligner therapy - Thu-Trang Pham; Hong Thuy Pham Thi; Cao Binh Tran; Ngoc Quang Dong; Viet Hoang (Journal of Orthodontic Science)
OBJECTIVES: This study aimed to determine the accuracy of overbite correction in patients with deep bite using the clear aligner therapy (CAT). MATERIALS AND METHODS: This retrospective study included 31 patients prescribed orthodontic treatment using CAT from January 2020 to January 2024. Clinical information was collected via X-ray results at pre-treatment and post-treatment stages. Treatment outcomes were measured at three stages: pre-treatment, post-treatment (clinical results), and predict treatment (predict results) as programmed in ClinCheck®. RESULTS: Significant changes were observed in X-ray in both overbite (3.85 ± 1.38 mm to 2.93 ± 1.13 mm) and overjet (5.19 ± 1.79 mm to 3.43 ± 1.14 mm) following CAT. For clinical crown lengthening (CCL) of tooth 31, significant differences were noted between pre-treatment and post-treatment (−0.31 ± 0.66 mm) and between predicted and clinical results (−0.21 ± 0.58 mm). For CCL of tooth 41, significant differences were found between pre-treatment and post-treatment (-0.36 ± 0.66 mm) and between prediction and post-treatment (−0.32 ± 0.65 mm). The percentage of deep bites differed significantly between pre-treatment vs predicted treatment (38.10 ± 14.90%), pre-treatment vs post-treatment (11.80 ± 14.30%), and predicted treatment vs post-treatment (−26.40 ± 12.60%). Similar trends were observed in mean overbite (2.77 ± 1.07 mm, 0.69 ± 0.93 mm, and − 2.08 ± 0.83 mm, respectively). CONCLUSIONS: Our findings support the use of CAT as a reliable and aesthetic option for treating deep bite malocclusions.